1960
DOI: 10.1021/ja01495a070
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL ANTICANCER AGENTS.1 XL. SYNTHESIS OF THE β-ANOMER OF 9-(D-ARABINOFURANOSYL)-ADENINE

Abstract: COMMUNICATIONS TO THE EDITORVol. s2(V) bromide a t the temperature necessary for synthesis (ca. 100') keeps the yield very low and that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(47 citation statements)
references
References 0 publications
0
45
0
2
Order By: Relevance
“…Perhaps the best examples for this comment are two very early drugs in this section, vidarabine (72) and acyclovir (73). In the first case, the change of the sugar to arabinose (as mentioned earlier, this was coincidental with the reports of the Bergmann group, though whether Lee et al, 34 had prior knowledge is unknown), yielded a compound that was designed to be an antitumor agent but gained fame as an anti-herpes simplex drug. Similarly, perhaps the most "famous" of these early nucleosides was azidothymidine (AZT; 74).…”
Section: Antiviral Agents Based On Nucleosidesmentioning
confidence: 58%
See 1 more Smart Citation
“…Perhaps the best examples for this comment are two very early drugs in this section, vidarabine (72) and acyclovir (73). In the first case, the change of the sugar to arabinose (as mentioned earlier, this was coincidental with the reports of the Bergmann group, though whether Lee et al, 34 had prior knowledge is unknown), yielded a compound that was designed to be an antitumor agent but gained fame as an anti-herpes simplex drug. Similarly, perhaps the most "famous" of these early nucleosides was azidothymidine (AZT; 74).…”
Section: Antiviral Agents Based On Nucleosidesmentioning
confidence: 58%
“…In a review in 1991, Suckling 33 demonstrated how such structures evolved in the Wellcome laboratories, leading ultimately to molecules such as azidothymidine (74) or 34 reported the synthesis of arabinosyladenine (Ara-A or vidarabine, 72) as a potential antitumor agent, with a later report showing production by fermentation of S. antibioticus. 35 Then it was isolated and purified from the Mediterranean gorgonian Eunicella cavolini by the Cimino et al 36 in 1984.…”
Section: Drugs Derived From Nucleosidesmentioning
confidence: 99%
“…40,41 Ara-C (4) é usada principalmente na terapia da leucemia aguda não linfoblástica, enquanto que ara-A (3) é utilizada 42 De acordo com Newman e Cragg, 10 o grande impacto da descoberta dessas moléculas foi demonstrar, pela primeira vez, a ocorrência de nucleosídeos naturais bioativos contendo açúcares diferentes da ribose e da deoxirribose. Pode-se dizer ainda que essa constatação deu origem a toda uma geração de nucleosídeos incomuns e não naturais com potencial terapêutico, incluindo o fármaco anti-HIV, azidotimidina ou AZT.…”
Section: Ara-c (Citarabina ® ) E Ara-a(vidarabina ® )unclassified
“…The synthesis (9,26) and biological inhibitory activity (27, 28) of 9-P-D-arabinofuranosyiadenine (araA) were reported several years before its isolation from microbiological culture fermentation (29) and evaluation as a promising antiviral drug (30). Synthetic 9-P-D-xylofuranosyladenine (xyloA) (46, 31) was also shown to exhibit inhibitory activity against neoplastic cells (32).…”
Section: -8-pivalyl-p-d-xylofuranosyl)pyrrolo[23 -D L -mentioning
confidence: 99%